Aktivitas Antibakteri Ekstrak Lumut Octoblepharum albidium Hedw terhadap Pertumbuhan Staphylococcus epidermidis dan Pseudomonas aeruginosa - Irwan Lovadi, Wiwid Widyana, Siti Khotimah, (Jurnal Protobiont, 2014)
Mosses are non-vascular plants groups and grow in a wide range of substrates. Mosses contain secondary metabolites that have antibacterial activity. This research aimed to determine the antibacterial activity of Octoblepharum albidium extract on the growth of Staphylococcus epidermidis and Pseudomonas aeruginosa. This research was performed in June until July 2013. The Qualitative phytochemical tests showed that O. albidium contains secondary metabolites such as alkaloids, polyphenols, flavonoids, saponins and terpenoids. The existence of secondary metabolites in O. albidium, could be utilized to inhibit the growth of bacteria S. epidermidis and P. aeruginosa. The testing of antibacterial activity has been performed using paper disk diffusion method with a concentration of 20%, 40%, 60%, 80%, 100% and a positive control of chloramphenicol 2.5% (g/ml). The antibacterial activity test result showed that all level of extract concentrations were able to inhibit the growth of bacteria that was characterized by the formation of inhibition zone around the paper disc. The activity of 100% extract consentration againts S.epidermidis and P. aeruginosa bacteria demonstrated the highest inhibition zone diameter, which was 15.62 mm and 13.23 mm, while the most effective extract concentrations in inhibiting S. epidermidis and P.aeruginosa are 60% and 80%, respectively.